Carlo Passaglia on Church and Virgin : New Perspectives in Systematic Theology in Light of Nineteenth Century Catholic Renewal - Rossi, Valfredo Maria, (Brill's Studies in Catholic Theology ;, 2020)
In Carlo Passaglia on Church and Virgin, Valfredo Maria Rossi traces the significant contribution that Carlo Passaglia (1812-1887) has made to Catholic theology, paying particular attention to his Trinitarian ecclesiology and Mariology. Though highly neglected due to his troubled life, Passaglia is one of the most brilliant theologians of the nineteenth century. Commonly - and yet erroneously - ascribed to the Neo-Scholastic movement, he anticipates and so emerges as a forerunner of several themes which will be developed during the Second Vatican Council. In light of Passaglia's two most relevant theological works ( De Ecclesia Christi and De Immaculato Deiparae semper Virginis Conceptu ), Rossi convincingly shows the originality of Passaglia's theology, based on a patristic ressourcement highlighting its historical salvific and sacramental dimension.